2016
DOI: 10.1038/srep26434
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium inference screw supports early graft incorporation with inhibition of graft degradation in anterior cruciate ligament reconstruction

Abstract: Patients after anterior cruciate ligament (ACL) reconstruction surgery commonly encounters graft failure in the initial phase of rehabilitation. The inhibition of graft degradation is crucial for the successful reconstruction of the ACL. Here, we used biodegradable high-purity magnesium (HP Mg) screws in the rabbit model of ACL reconstruction with titanium (Ti) screws as a control and analyzed the graft degradation and screw corrosion using direct pull-out tests, microCT scanning, and histological and immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 45 publications
(47 reference statements)
1
38
0
Order By: Relevance
“…As being a key component of the ribosomal machinery that translates genetic information encoded by mRNA into polypeptide structures, we hypothesized that relatively high concentrations of magnesium could enhance the protein translation for the extracellular matrix such as collagens I and III 12 . Results of our study were consistent with various other research findings 39 40 41 . A variety of cytokines such as interleukin-1 (IL-1) and tumor necrosis factor α (TNF-α) play an important role in the expression of MMPs 42 43 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As being a key component of the ribosomal machinery that translates genetic information encoded by mRNA into polypeptide structures, we hypothesized that relatively high concentrations of magnesium could enhance the protein translation for the extracellular matrix such as collagens I and III 12 . Results of our study were consistent with various other research findings 39 40 41 . A variety of cytokines such as interleukin-1 (IL-1) and tumor necrosis factor α (TNF-α) play an important role in the expression of MMPs 42 43 .…”
Section: Discussionsupporting
confidence: 93%
“…As magnesium could inhibit intracellular calcium influx, reduces mitochondrial calcium overload, and conserves intracellular adenosine triphosphate (ATP) as ionized Mg-ATP, we hypothesized that increased extracellular magnesium may have a protective effect by decreasing the secretion of interleukins during ischemia in the anastomotic healing. In another frontier study, the researchers hypothesized that Mg ion released from corroded Mg screws blocked MMP-13 expression, inhibited the degradation of collagens via tyrosine kinase inhibitors through a highlighted signaling pathway 41 . In previous researches, it was demonstrated that extracellular Mg reduced MMPs in a dose-dependent manner in cultured rat vascular smooth muscle cells as well as rat cardiac fibroblasts potentially via two tyrosine kinase inhibitors, genistein and herbimycin A 44 45 .…”
Section: Discussionmentioning
confidence: 99%
“…has also recently used Mg interference screws to fix tendon graft into bone tunnels in a rabbit model of ACL reconstruction26. Although our animal model is similar to Cheng’s model, the research interests of Cheng PF’s and our studies are different.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al . also found that Mg interference screws could effectively inhibit the degeneration of the tendon graft during the remodeling phase via reducing the expression level of MMP-13, indicating that more collagen fibers in the tendon graft were preserved to connect the surrounding bone tissue for higher knee stability26. However, it is still unclear if Mg based fixators can also promote graft healing at the mid-tunnel interface as spatial differences in tendon-bone healing in a bone tunnel was reported27.…”
mentioning
confidence: 99%
“…Interference screws are used to fix tendon graft with a bone tunnel in anterior cruciate ligament (ACL) construction. Cheng et al [32] reported that the high-purity magnesium (HP–Mg) showed good cytocompatibility and promoted the expression of bone morphogenetic protein-2 (BMP-2) and vascular endothelial growth factor (VEGF), fibrocartilage markers (Aggrecan, COL2A1, and SOX-9), and glycosaminoglycan (GAG) production in vitro cell culture tests. Then they used the HP-Mg interference screw to fix the semitendinosus autograft to the femoral tunnel in a rabbit model of ACL reconstruction with titanium screw as the control.…”
Section: Orthopedic Implantsmentioning
confidence: 99%